Thermodynamics, Kinetics and Mechanisms of Noncompetitive Allosteric Inhibition of Chymotrypsin by Dihydrolipoic Acid-Coated Gold Nanoclusters - Chen, Wen-Qi (Langmuir : the ACS journal of surfaces and colloids, 2020)
Enzymes are an important class of biomacromolecules which catalyze many metabolic processes in living systems. Nanomaterials can be synthesized with tailored sizes as well as desired surface modifications, thus acting as promising enzyme regulators. Fluorescent gold nanoclusters (AuNCs) are a representative class of ultrasmall nanoparticles (USNPs) with sizes of ∼2 nm, smaller than most of proteins including enzymes. In this work, we chose α-chymotrypsin (ChT) and AuNCs as the model system. Activity assays and inhibition kinetics studies showed that dihydrolipoic acid (DHLA)-coated AuNCs (DHLA-AuNCs) had a high inhibitory potency (IC50 = 3.4 μM) and high inhibitory efficacy (>80%) on ChT activity through noncompetitive inhibition mechanism. In distinct contrast, glutathione (GSH)-coated AuNCs (GSH-AuNCs) had no significant inhibition effects. Fluorescence spectroscopy, agarose gel electrophoresis and circular dichroism (CD) spectroscopy were conducted to explore the underlying mechanisms. A two-step interaction model was proposed. First, both DHLA-AuNCs and GSH-AuNCs might be bound to the positively charged sites of ChT through electrostatic forces. Second, further hydrophobic interactions occurred between three tyrosine residues of ChT and the hydrophobic carbon chain of DHLA, leading to a significant structural change thus to deactivate ChT on the allosteric site. On the contrary, no such interactions occurred with GSH of zwitterionic characteristic, which explained no inhibitory effect of GSH-AuNCs on ChT. To the best of our knowledge, this is the first example of the allosteric inhibition of ChT by nano regulators. These findings provide a fundamental basis for the design and development of nano regulators